Thermal Stability Analysis of Cellulose From Sago Fiber Waste (Metroxylon sago) - Nurmalasari, Nurmalasari; Lestari, Sastriana Jaya; Syamsuddin, Mimi; Sukarti, Sukarti; Alam, Muhammad Nur (EduChemia: Jurnal Kimia dan Pendidikan, 2022)
Sago pulp is a lignocellulosic waste rich in cellulose, so that it can be used optimally as a source of carbon and cellulose. Fixed carbon can be obtained maximally by determining the carbonization temperature. This research aims to determine the temperature of the cellulose sample starting to decompose and the energy required at the time of decomposition. The process of extracting cellulose from sago fiber waste uses NaOH alkalinization for delignification, bleaching with H2O2, and hydrolysis with HCl. Identification of lignin in sago fiber is known by the appearance of the C=O group in the wave region of 1734.01 cm-1 with strong intensity; after extraction, no peak number was found in the extracted cellulose FTIR spectrum. TGA analysis of cellulose underwent two stages of mass change, the first stage of decomposition of water molecules at a temperature of 47°C-203°C obtained a mass decrease of 5.69%, and the second stage of decomposition at a temperature of 287°C-397°C obtained a mass decrease of 58.95%. DSC analysis obtained two thermal properties of physical changes contained in two endothermic peaks, the first peak of water evaporation which required energy of 28,1120 J/g, and the second peak of decomposition, which required energy of 9.6188 J/g.